2004
DOI: 10.1152/ajpendo.00295.2003
|View full text |Cite
|
Sign up to set email alerts
|

Onset of diabetes in Zucker diabetic fatty (ZDF) rats leads to improved recovery of function after ischemia in the isolated perfused heart

Abstract: The aim of this study was to determine whether the transition from insulin resistance to hyperglycemia in a model of type 2 diabetes leads to intrinsic changes in the myocardium that increase the sensitivity to ischemic injury. Hearts from 6-, 12-, and 24-wk-old lean (Control) and obese Zucker diabetic fatty (ZDF) rats were isolated, perfused, and subjected to 30 min of low-flow ischemia (LFI) and 60 min of reperfusion. At 6 wk, ZDF animals were insulin resistant but not hyperglycemic. By 12 wk, the ZDF group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
64
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 47 publications
(64 reference statements)
15
64
2
2
Order By: Relevance
“…The present study in Type 2 diabetes demonstrates that hearts from diabetic rats are protected against ischaemic damage because infarct size was smaller in both obese and lean diabetic animals than in non-diabetic animals. However, in contrast to a recent study demonstrating increased post-ischaemic left ventricular recovery after low-flow ischaemia [14], our data show no improvement of post ischaemic left ventricular function in Type 2 diabetic animals, although infarct size, compared to non-diabetic control animals, was smaller, suggesting a contractile dysfunction in non-infarcted diabetic myocardium. This is supported by a previous study [15], which reported a dissociation between protection against isoproterenol-induced myocardial fibrosis and the haemodynamic response, which was unaffected in a model of Type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study in Type 2 diabetes demonstrates that hearts from diabetic rats are protected against ischaemic damage because infarct size was smaller in both obese and lean diabetic animals than in non-diabetic animals. However, in contrast to a recent study demonstrating increased post-ischaemic left ventricular recovery after low-flow ischaemia [14], our data show no improvement of post ischaemic left ventricular function in Type 2 diabetic animals, although infarct size, compared to non-diabetic control animals, was smaller, suggesting a contractile dysfunction in non-infarcted diabetic myocardium. This is supported by a previous study [15], which reported a dissociation between protection against isoproterenol-induced myocardial fibrosis and the haemodynamic response, which was unaffected in a model of Type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…This agrees well with results obtained ex-vivo [5][6][7] and in-vivo [4,8,9] in rats fed a HF diet. However, this is in total opposition with the results from ZDF rats [13,14] and SMC-fed animals [2,3]. Yet, the two last situations are associated with increased blood glucose, whereas the increased chow intake was not in our study.…”
Section: Cardiac Function During Ischemia/reperfusioncontrasting
confidence: 99%
“…This confirms the effect of IAA in different ex-vivo models, including in Western diet-fed rats [5,7], ZDF animals [13,14,45] and mice subjected to ON [11]. This phenomenon was associated with lower coronary flow and cardiac metabolic efficiency.…”
Section: Cardiac Function With Pre-ischemic Conditionssupporting
confidence: 77%
See 2 more Smart Citations